3D printed concrete blocks made with sustainable recycled material
The use of recovered materials in building construction is one of the most effective strategies for reducing the environmental impacts of the construction sector. Innovative technologies such as 3D construction printing can be applied in combination with recycling strategies in order to optimise their performances also from an environmental point of view. In fact, several studies have proposed the processing of waste material into printable material. At the same time, performance studies must be conducted on the building components produced by these methods. This study proposes a methodological approach to design a 3D printable building component made with recycled materials considering the improvement of thermal performances. In particular, the approach is based on three steps: reuse strategy conception; target performance definition, modelling and iterative simulation; 3D printing setting. The methodological approach has been applied to a 3D printable block using as printable material a cement-based mortar with recycled aggregates and recycled insulating material. As a result, the component's shape (interlocking and inspired by honeycombs) can be customised to achieve the required thermal performance by using recycled materials in the printing process.